Seismic prediction of shale reservoir quality parameters: A case study of the Longmaxi–Wufeng formation in the WY area - Hu, Xiuquan; Yu, Wanli; Yi, Chi; Xiao, Chenjing; Li, Jianghan; Wang, Boqiang (Frontiers in Earth Science, 2023)
Shale is a crucial natural gas resource, attracting global exploration and development interest. China has abundant shale gas resources that will drive future oil and gas exploration advances by increasing reserves and production. The WY shale gas field is the most productive and has the greatest potential for exploration and development. This study analyzed high-quality shale logging response characteristics and drilling logging, seismic, and analytical test data in the WY area to establish a rock physical model of seismic attribute parameters and shale reservoir quality parameters. Seismic elastic parameters were converted into indicators that directly reflect shale reservoir quality, such as total organic carbon (TOC), high-quality reservoir thickness, porosity, brittleness index, and crack development strength. Corresponding regression equations were established to predict quality parameters.The results showed that shale reservoir quality parameters have a good correlation with seismic parameters. The TOC distribution ranged from 2% to 5% in the study area and was generally high in the north but low in the south. The high-quality shale reserve had a thickness of over 40 meters, and except for the northwest region, the porosity was nearly over 4%. The overall brittleness of the study area was favorable, and the brittleness index was over 35%, which is suitable for network fractures formation in subsequent fracturing operations. The anisotropy of shale in S1l1I was small, and the overall fractures were underdeveloped in the study area. Drilling verifications showed that the prediction results of the quality parameters of high-quality shale reservoirs were consistent with actual drilling test results with high reliability. This study provides guidance for comprehensive prediction of sweet spots and subsequent fracturing and well location deployment.In summary, this study provides valuable insights into shale gas exploration and development in the WY area by establishing a rock physical model, predicting quality parameters, and offering guidance for fracturing and well location deployment.